Modified coal gangue adsorbent as well as preparation method and application thereof

Through calcination treatment and oxidation treatment of thiolsilane compounds, the pollution in the preparation process of modified coal gangue adsorbent is reduced and the adsorption efficiency is improved. The problems of pollution and adsorption efficiency in the preparation process in the prior art are solved, and the lower cost and more efficient adsorption of heavy metal ions are achieved.

CN119701868APending Publication Date: 2025-03-28SHENHUA XINJIE ENERGY +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411792226.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The preparation process of existing modified coal gangue adsorbents is highly polluted and has low adsorption efficiency, high production costs, and difficult to achieve industrialization.

Method used

By mixing coal gangue with activator and calcining, a rich pore structure is formed, and then second mixing and oxidizing treatment is performed with thiol silane compounds, the -SH group is grafted and oxidized into -SO3H group, thereby improving adsorption performance.

Benefits of technology

The adsorption capacity of modified coal gangue adsorbents to heavy metal ions is improved, the steps of chemical modification are simplified, energy consumption and production costs are reduced, and pollution is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005175581270000081
    Figure BDA0005175581270000081
Patent Text Reader

Abstract

The invention provides a modified coal gangue adsorbent as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, sequentially carrying out first mixing, roasting treatment and impurity removal treatment on raw materials comprising coal gangue and an activating agent to obtain a first intermediate product; and S2, sequentially carrying out second mixing and oxidation treatment on raw materials comprising the first intermediate product, a sulfydryl silane compound and water to obtain the modified coal gangue adsorbent. The-SO3H group can be ionized in an aqueous solution to generate a large number of negative charges, and can adsorb the heavy metal ions with positive charges, so that the adsorbability of the modified coal gangue adsorbent to the heavy metal ions is improved. The adsorption capacity of the modified coal gangue to heavy metals is improved by constructing physical adsorption sites and chemical adsorption sites in the coal gangue, the chemical modification step is simplified, and the energy consumption of the modification process and the production cost of the modified coal gangue adsorbent are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adsorbents, and in particular to a modified coal gangue adsorbent and a preparation method and application thereof. Background Art

[0002] There are a lot of studies in the prior art on the use of modified coal gangue for the adsorption of heavy metal ions. However, there are still some problems in the modification of coal gangue and the use of modified coal gangue as an adsorbent. For example, a Chinese paper entitled "Study on the Adsorption Performance of Modified Coal Gangue on Cr(VI) in Water" improves the physical adsorption capacity of coal gangue by forming a rich pore structure inside the coal gangue, but there are still problems such as limited adsorption capacity and easy desorption to cause secondary pollution.

[0003] A Chinese patent application with patent application publication number CN202211421401A discloses a modified coal gangue adsorbent, a preparation method and application thereof, and a coal gangue-based adsorbent with strong cadmium ion adsorption capacity is prepared. However, the preparation process involves calcination, acidification, silanization, graphene oxide addition, arginine addition and roasting, and requires the use of KH560, graphene oxide, arginine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and other agents, resulting in complicated production process and high production cost, making it difficult to industrialize the adsorbent production.

[0004] Therefore, it is urgent to develop a new modified coal gangue adsorbent to solve the above problems. Summary of the invention

[0005] The main purpose of the present invention is to provide a modified coal gangue adsorbent and a preparation method and application thereof, so as to solve the problems in the prior art that the preparation process of the modified coal gangue adsorbent is highly polluting and the adsorption efficiency of the modified coal gangue adsorbent is low.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a modified coal gangue adsorbent is provided, and the preparation method comprises the following steps: step S1, sequentially subjecting raw materials including coal gangue and an activator to a first mixing, roasting treatment and impurity removal treatment to obtain a first intermediate product; step S2, sequentially subjecting raw materials including the first intermediate product, a mercaptosilane compound and water to a second mixing and oxidation treatment to obtain a modified coal gangue adsorbent.

[0007] Furthermore, in the above step S2, the ratio of the mass of the first intermediate product, the volume of the mercaptosilane compound and the volume of water is 1g:0.5~1mL:3~6mL; preferably, the mercaptosilane compound is 3-mercaptopropyltrimethoxysilane and / or 3-mercaptopropyltriethoxysilane.

[0008] Furthermore, in the above step S2, ball milling is used for the second mixing; the rotation speed of the ball milling is 200 to 300 rpm; and / or the ball milling time is 2 to 3 hours.

[0009] Further, in the above step S2, the oxidation treatment includes: stirring, washing and drying the raw materials including the second mixed product and the oxidant in sequence to obtain a modified coal gangue adsorbent; and / or, the stirring temperature is 20 to 30°C; and / or, the stirring time is 10 to 15 hours; and / or, the stirring speed is 100 to 300 rpm; preferably, the oxidant is selected from any one or more of a hydrogen peroxide solution, a potassium permanganate solution and a sodium hypochlorite solution; further preferably, the oxidant is a hydrogen peroxide solution; and / or, the mass concentration of hydrogen peroxide in the hydrogen peroxide solution is 10 to 30%; and / or, the ratio of the mass of the second mixed product to the volume of the hydrogen peroxide solution is 1g:15 to 30mL.

[0010] Furthermore, in the above step S2, the second mixed product is sequentially washed and dried, and then subjected to oxidation treatment.

[0011] Furthermore, in the above step S1, the particle size of the coal gangue does not exceed 200 mesh, preferably 300 mesh to 200 mesh; and / or the mass ratio of coal gangue to activator is 10:2 to 4; preferably, the activator is selected from any one or more of zinc chloride, ferrous chloride, cobalt chloride and nickel chloride.

[0012] Furthermore, in the above step S1, the temperature of the calcination treatment is 600-800° C.; and / or the time of the calcination treatment is 40-80 min.

[0013] Furthermore, in the above step S1, the impurity removal treatment includes: acid soaking, water washing and drying the product of the roasting treatment in sequence to obtain a first intermediate product; preferably, the acid soaking reagent is selected from any one or more of hydrochloric acid solution, sulfuric acid solution, phosphoric acid solution and acetic acid solution; further preferably, the acid soaking reagent is hydrochloric acid solution, and the concentration of hydrochloric acid in the hydrochloric acid solution is 1 to 3 mol / L; and / or, the ratio of the mass of the roasting product to the volume of the hydrochloric acid solution is 1g:5 to 10gmL; and / or, the acid soaking temperature is 20 to 30°C; and / or, the acid soaking time is 1 to 2h.

[0014] According to another aspect of the present invention, a modified coal gangue adsorbent is provided. The modified coal gangue adsorbent is prepared by the aforementioned preparation method.

[0015] According to another aspect of the present invention, there is provided a use of the aforementioned modified coal gangue adsorbent in wastewater treatment.

[0016] By applying the technical solution of the present application, in step S1, by mixing the gangue with the activator and then calcining it, it is helpful to make the pores of the gangue richer and looser, and to form more Si-O and Al-O defect sites in the clay minerals therein, which is helpful to improve the adsorption performance of the modified gangue adsorbent. In step S2, by performing a second mixing of the first intermediate product and the mercaptosilane compound, -SH groups are grafted inside the gangue, and the -SH groups are oxidized to -SO3H groups by oxidation treatment. The -SO3H groups can be ionized in aqueous solution to produce a large amount of negative charges, and can adsorb positively charged heavy metal ions, thereby helping to improve the adsorption of the modified gangue adsorbent to heavy metal ions. The present application improves the adsorption capacity of the modified gangue to heavy metals by constructing physical adsorption sites and chemical adsorption sites in the gangue, and simplifies the steps of chemical modification, reducing the energy consumption of the modification process and the production cost of the modified gangue adsorbent. DETAILED DESCRIPTION

[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0018] As analyzed in the background technology of this application, the preparation process of modified coal gangue adsorbent in the prior art is highly polluting and the adsorption efficiency of the modified coal gangue adsorbent is low. In order to solve this problem, this application provides a modified coal gangue adsorbent and its preparation method and application.

[0019] In a typical embodiment of the present application, a method for preparing a modified gangue adsorbent is provided, and the preparation method comprises the following steps: step S1, sequentially performing a first mixing, roasting and impurity removal treatment on a raw material including gangue and an activator to obtain a first intermediate product; step S2, sequentially performing a second mixing and oxidation treatment on a raw material including the first intermediate product, a mercaptosilane compound and water to obtain a modified gangue adsorbent.

[0020] In step S1, by mixing the gangue with the activator and then calcining it, it helps to make the pores of the gangue richer and looser, and the clay minerals therein form more Si-O and Al-O defect sites, which helps to improve the adsorption performance of the modified gangue adsorbent. In step S2, by performing a second mixing of the first intermediate product and the mercaptosilane compound, -SH groups are grafted inside the gangue, and the -SH groups are oxidized to -SO3H groups through oxidation treatment. The -SO3H groups can be ionized in aqueous solution to produce a large amount of negative charges, and can adsorb positively charged heavy metal ions, thereby helping to improve the adsorption of the modified gangue adsorbent to heavy metal ions. The present application improves the adsorption capacity of the modified gangue to heavy metals by constructing physical adsorption sites and chemical adsorption sites in the gangue, simplifies the steps of chemical modification, and reduces the energy consumption of the modification process and the production cost of the modified gangue adsorbent.

[0021] In one embodiment of the present application, in the above step S2, the ratio of the mass of the first intermediate product, the volume of the mercaptosilane compound and the volume of water is 1g:0.5~1mL:3~6mL; preferably, the mercaptosilane compound is 3-mercaptopropyltrimethoxysilane and / or 3-mercaptopropyltriethoxysilane.

[0022] It is preferred to control the mass of the first intermediate product, the volume ratio of the mercaptosilane compound and the volume ratio of water within the above range, which helps to control the number of -SH groups grafted into the interior of the gangue and improve the dispersion uniformity of the -SH groups, thereby helping to improve the adsorption efficiency of the modified gangue adsorbent for heavy metal ions. It is preferred to control the type of mercaptosilane compound within the above range, which helps to improve the stability of the -SH group inside the gangue, thereby helping to further improve the adsorption amount of the modified gangue adsorbent for heavy metal ions.

[0023] In one embodiment of the present application, in the above step S2, ball milling is used for the second mixing; the rotation speed of the ball milling is 200-300 rpm; and / or the ball milling time is 2-3 hours.

[0024] Preferably, the rotation speed and time of ball milling are controlled within the above range, which helps to generate sufficient mechanical force, promotes full contact and uniform dispersion between the first intermediate product and the mercaptosilane compound, helps to improve the efficiency of -SH group grafting to the inside of coal gangue, and improves the uniformity of distribution of active sites of modified coal gangue adsorbent, thereby helping to enhance the chemical adsorption capacity of modified coal gangue adsorbent, and improve the adsorption efficiency and capacity of modified coal gangue adsorbent. Preferably, ball milling uses a planetary ball mill.

[0025] In one embodiment of the present application, in the above step S2, the oxidation treatment includes: stirring, washing and drying the raw materials including the second mixed product and the oxidant in sequence to obtain a modified coal gangue adsorbent; and / or, the stirring temperature is 20 to 30°C; and / or, the stirring time is 10 to 15 hours; and / or, the stirring speed is 100 to 300 rpm; preferably, the oxidant is selected from any one or more of a hydrogen peroxide solution, a potassium permanganate solution and a sodium hypochlorite solution; further preferably, the oxidant is a hydrogen peroxide solution; and / or, the mass concentration of hydrogen peroxide in the hydrogen peroxide solution is 10 to 30%; and / or, the ratio of the mass of the second mixed product to the volume of the hydrogen peroxide solution is 1g:15 to 30mL.

[0026] Preferably, the temperature, time and speed of the stirring treatment are controlled within the above ranges, which helps to reduce the generation of by-products while improving the oxidation efficiency of the -SH group. Controlling the mass concentration of hydrogen peroxide in the hydrogen peroxide solution and the ratio of the mass of the second mixed product to the volume of the hydrogen peroxide solution within the above ranges helps to further improve the oxidation efficiency while reducing the probability of over-oxidation. Preferably, the oxidant is a hydrogen peroxide solution, which helps to reduce the pollution of the reagent to the environment. Excess hydrogen peroxide is removed by washing with water, preferably washing with water until the pH of the washing liquid is 7, and drying at 70-80°C for 8-12 hours.

[0027] In one embodiment of the present application, in the above step S2, the second mixed product is sequentially washed and dried, and then subjected to oxidation treatment.

[0028] The ungrafted mercaptosilane compounds on the surface of the second mixed product are removed by water washing. Preferably, the water washing is to wash the second mixed product with distilled water for 3 to 5 times and dry it at 70 to 80° C. for 8 to 12 hours.

[0029] In one embodiment of the present application, in the above step S1, the particle size of the coal gangue does not exceed 200 mesh, preferably 300 mesh to 200 mesh; and / or the mass ratio of the coal gangue to the activator is 10:2 to 4; preferably, the activator is selected from any one or more of zinc chloride, ferrous chloride, cobalt chloride and nickel chloride.

[0030] Controlling the particle size of the gangue within the above range helps to increase the specific surface area of ​​the gangue while reducing the agglomeration of the gangue, and helps to provide more active sites for subsequent chemical modification. Preferably, controlling the mass ratio of the gangue to the activator within the above range helps to promote the optimization of the pore structure of the gangue and form a structure rich in defect sites, thereby helping to further improve the adsorption activity of the modified gangue adsorbent. Preferably, controlling the type of the activator within the above range helps to further improve the adsorption amount of the modified gangue adsorbent for heavy metal ions.

[0031] In one embodiment of the present application, in the above step S1, the temperature of the calcination treatment is 600-800° C.; and / or the time of the calcination treatment is 40-80 min.

[0032] At high temperatures, organic matter and some minerals in the gangue will decompose to form microporous and mesoporous structures, which helps to increase the specific surface area of ​​the gangue. It is preferred to control the temperature and time of the roasting treatment within the above range, which helps to promote the reorganization and optimization of the internal structure of the gangue, while maintaining the stability of the gangue structure and increasing the active sites on the surface of the gangue.

[0033] In one embodiment of the present application, in the above-mentioned step S1, the impurity removal treatment includes: acid soaking, water washing and drying the product of the roasting treatment in sequence to obtain a first intermediate product; preferably, the acid soaking reagent is selected from any one or more of hydrochloric acid solution, sulfuric acid solution, phosphoric acid solution and acetic acid solution; further preferably, the acid soaking reagent is a hydrochloric acid solution, and the concentration of hydrochloric acid in the hydrochloric acid solution is 1 to 3 mol / L; and / or, the ratio of the mass of the roasting product to the volume of the hydrochloric acid solution is 1g:5 to 10gmL; and / or, the acid soaking temperature is 20 to 30°C; and / or, the acid soaking time is 1 to 2h.

[0034] Acid soaking helps to remove impurities and inactive components on the surface of gangue, such as minerals, organic residues, etc. These impurities may interfere with the subsequent chemical modification process and reduce the activity and selectivity of the adsorbent. It is preferred to control the concentration of hydrochloric acid in the hydrochloric acid solution, the ratio of the mass of the roasted product to the volume of the hydrochloric acid solution, and the temperature and time of acid soaking within the above range, which helps to improve the efficiency of impurity removal while maintaining the structural stability of the gangue. It is preferred to wash with water until the pH of the washing liquid is 7, and dry at 70-80°C for 8-12 hours.

[0035] In another typical embodiment of the present application, a modified coal gangue adsorbent is provided. The modified coal gangue adsorbent is prepared by the aforementioned preparation method.

[0036] The modified coal gangue adsorbent prepared by the preparation method of the present application has a high adsorption capacity for heavy metal ions.

[0037] In another typical embodiment of the present application, there is provided a use of the aforementioned modified coal gangue adsorbent in wastewater treatment.

[0038] The modified coal gangue adsorbent of the present application has a good adsorption effect on heavy metal ions in wastewater.

[0039] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0040] Example 1

[0041] 1) Calcination treatment: crush the coal gangue, screen the coal gangue particles with a particle size between 200 and 300 meshes, mix them with zinc chloride in a mass ratio of 10:3, and roast the mixture at 700° C. for 80 min. After roasting, soak it in a 3 mol / L hydrochloric acid solution for 2 h, then wash the precipitate with water until the pH of the washing liquid is 7, and dry it at 80° C. for 8 h to obtain a first intermediate product;

[0042] 2) Wet ball milling: The first intermediate product, 3-mercaptopropyltrimethoxysilane and water are wet-milled with a planetary ball mill, wherein the mass of the first intermediate product is 5 g, the amount of 3-mercaptopropyltrimethoxysilane added is 5 mL, the amount of water added is 30 mL, the ball mill speed is set to 300 rpm, the ball milling time is 2 h, and after the ball milling, it is washed with distilled water 3 times and dried at 80 ° C for 8 h to obtain a second intermediate product.

[0043] 3) Low-temperature oxidation: 10 g of the second intermediate product was placed in hydrogen peroxide and stirred at 30°C, wherein the mass concentration of hydrogen peroxide was 30%, the volume of hydrogen peroxide was 250 mL, the treatment time was 14 h, the stirring speed was 300 r / min, and after the treatment, the precipitate was washed with water until the pH of the washing liquid was 7, and dried at 80°C for 8 h to obtain a modified coal gangue adsorbent.

[0044] Example 2

[0045] The difference from Example 1 is that 1) calcination treatment: crush the coal gangue, screen the coal gangue particles with a particle size between 200 and 300 meshes, and then mix them with zinc chloride in a mass ratio of 10:2, and calcine the mixture at 600°C for 60 minutes. After calcination, soak it in a 2 mol / L hydrochloric acid solution for 1 hour, then wash the precipitate with water until the pH of the washing liquid is 7, and dry it at 80°C for 8 hours to obtain a first intermediate product;

[0046] 2) Wet ball milling: The first intermediate product, 3-mercaptopropyltrimethoxysilane and water were wet-milled with a planetary ball mill, wherein the mass of the first intermediate product was 5 g, the amount of 3-mercaptopropyltrimethoxysilane added was 5 mL, the amount of water added was 15 mL, the ball mill speed was set to 200 rpm, the ball milling time was 2 h, and after the ball milling, it was washed with distilled water 3 times and dried at 80 ° C for 8 h to obtain a second intermediate product.

[0047] 3) Low-temperature oxidation: 10 g of the second intermediate product was placed in hydrogen peroxide and stirred at 20°C, wherein the mass concentration of hydrogen peroxide was 30%, the volume of hydrogen peroxide was 200 mL, the treatment time was 12 h, the stirring speed was 200 r / min, and after the treatment, the precipitate was washed with water until the pH of the washing liquid was 7, and dried at 80°C for 8 h to obtain a modified coal gangue adsorbent.

[0048] Example 3

[0049] The difference from Example 1 is that the added amount of 3-mercaptopropyltrimethoxysilane is 5 mL, and the added amount of water is 15 mL, and finally a modified coal gangue adsorbent is obtained.

[0050] Example 4

[0051] The difference from Example 1 is that the added amount of 3-mercaptopropyltrimethoxysilane is 2.5 mL, and the added amount of water is 30 mL, and finally a modified coal gangue adsorbent is obtained.

[0052] Example 5

[0053] The difference from Example 1 is that the added amount of 3-mercaptopropyltrimethoxysilane is 1.5 mL, and the added amount of water is 12 mL, and finally a modified coal gangue adsorbent is obtained.

[0054] Example 6

[0055] The difference from Example 1 is that 3-mercaptopropyltriethoxysilane is used to replace 3-mercaptopropyltrimethoxysilane, and finally a modified coal gangue adsorbent is obtained.

[0056] Example 7

[0057] The difference from Example 1 is that the ball milling speed is 300 rpm, the ball milling time is 3 h, and finally a modified coal gangue adsorbent is obtained.

[0058] Example 8

[0059] The difference from Example 1 is that the rotation speed of the ball mill is 100 rpm, the ball milling time is 1 hour, and finally a modified coal gangue adsorbent is obtained.

[0060] Example 9

[0061] The difference from Example 1 is that the volume of hydrogen peroxide is 150 mL, and a modified coal gangue adsorbent is finally obtained.

[0062] Example 10

[0063] The difference from Example 1 is that the volume of hydrogen peroxide is 300 mL, and a modified coal gangue adsorbent is finally obtained.

[0064] Embodiment 11

[0065] The difference from Example 1 is that the volume of hydrogen peroxide is 100 mL, and a modified coal gangue adsorbent is finally obtained.

[0066] Example 12

[0067] The difference from Example 1 is that the stirring treatment time is 15 hours, the stirring treatment speed is 300 r / min, and finally a modified coal gangue adsorbent is obtained.

[0068] Example 13

[0069] The difference from Example 1 is that the stirring treatment time is 10 h, the stirring treatment speed is 100 r / min, and finally a modified coal gangue adsorbent is obtained.

[0070] Embodiment 14

[0071] The difference from Example 1 is that the stirring treatment time is 8 hours, the stirring treatment speed is 50 r / min, and finally a modified coal gangue adsorbent is obtained.

[0072] Embodiment 15

[0073] The difference from Example 1 is that the mass ratio of coal gangue to zinc chloride is 10:4, and a modified coal gangue adsorbent is finally obtained.

[0074] Example 16

[0075] The difference from Example 1 is that the mass ratio of coal gangue to zinc chloride is 10:1, and a modified coal gangue adsorbent is finally obtained.

[0076] Embodiment 17

[0077] The difference from Example 1 is that the calcination temperature is 800° C., the calcination time is 40 min, and finally a modified coal gangue adsorbent is obtained.

[0078] Embodiment 18

[0079] The difference from Example 1 is that the calcination temperature is 550° C., the calcination time is 30 min, and finally a modified coal gangue adsorbent is obtained.

[0080] Comparative Example 1

[0081] The gangue was crushed and sieved to obtain gangue particles with a particle size between 200 and 300 meshes, and then mixed with zinc chloride in a mass ratio of 10:2. The mixture was calcined at 600°C for 80 min, and after calcination, it was immersed in a 2 mol / L hydrochloric acid solution for 1 h. The precipitate was then washed with water until the pH value of the washing liquid was 7, and dried at 80°C for 8 h to obtain a modified gangue adsorbent.

[0082] Comparative Example 2

[0083] The difference from Example 1 is that low-temperature oxidation is not performed, and a modified coal gangue adsorbent is finally obtained.

[0084] Comparative Example 3

[0085] The difference from Example 1 is that zinc chloride is not added, and a modified coal gangue adsorbent is finally obtained.

[0086] Performance Testing

[0087] 0.5 g of the modified gangue adsorbent prepared in the above embodiments and comparative examples was added to 30 mL of Cr(VI) wastewater with an initial concentration of 50 mg / L, and oscillated at a constant temperature for 2 h. The equilibrium adsorption amount and removal rate of Cr(VI) in wastewater by the modified gangue adsorbent prepared in the embodiments and comparative examples were measured. The measurement results are shown in Table 1.

[0088] Table 1

[0089]

[0090] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0091] In step S1, by mixing the gangue with the activator and then calcining it, it helps to make the pores of the gangue richer and looser, and the clay minerals therein form more Si-O and Al-O defect sites, which helps to improve the adsorption performance of the modified gangue adsorbent. In step S2, by performing a second mixing of the first intermediate product and the mercaptosilane compound, -SH groups are grafted inside the gangue, and the -SH groups are oxidized to -SO3H groups through oxidation treatment. The -SO3H groups can be ionized in aqueous solution to produce a large amount of negative charges, and can adsorb positively charged heavy metal ions, thereby helping to improve the adsorption of the modified gangue adsorbent to heavy metal ions. The present application improves the adsorption capacity of the modified gangue to heavy metals by constructing physical adsorption sites and chemical adsorption sites in the gangue, simplifies the steps of chemical modification, and reduces the energy consumption of the modification process and the production cost of the modified gangue adsorbent.

[0092] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified coal gangue adsorbent, characterized in that: The preparation method comprises the following steps: Step S1, sequentially performing a first mixing, roasting and impurity removal treatment on the raw materials including coal gangue and an activator to obtain a first intermediate product; Step S2, subjecting the raw materials including the first intermediate product, the mercaptosilane compound and water to a second mixing and oxidation treatment in sequence to obtain the modified coal gangue adsorbent.

2. The preparation method according to claim 1, characterized in that: In step S2, the ratio of the mass of the first intermediate product, the volume of the mercaptosilane compound and the volume of the water is 1g:0.5-1mL:3-6mL; preferably, the mercaptosilane compound is 3-mercaptopropyltrimethoxysilane and / or 3-mercaptopropyltriethoxysilane.

3. The preparation method according to claim 1 or 2, characterized in that: In the step S2, the second mixing is performed by ball milling; the rotation speed of the ball milling is 200 to 300 rpm; and / or the time of the ball milling is 2 to 3 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that In the step S2, the oxidation treatment includes: stirring, washing and drying the raw materials including the second mixed product and the oxidant in sequence to obtain the modified coal gangue adsorbent; and / or, the stirring temperature is 20-30° C.; and / or, the stirring time is 10-15 hours; and / or, the stirring speed is 100-300 rpm; Preferably, the oxidant is selected from any one or more of a hydrogen peroxide solution, a potassium permanganate solution and a sodium hypochlorite solution; further preferably, the oxidant is a hydrogen peroxide solution; and / or the mass concentration of hydrogen peroxide in the hydrogen peroxide solution is 10 to 30%; And / or, the ratio of the mass of the second mixed product to the volume of the hydrogen peroxide solution is 1 g: 15-30 mL.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step S2, the second mixed product is sequentially washed with water and dried, and then subjected to the oxidation treatment.

6. The preparation method according to any one of claims 1 to 5, characterized in that In the step S1, the particle size of the coal gangue does not exceed 200 mesh, preferably 300 mesh to 200 mesh; and / or the mass ratio of the coal gangue to the activator is 10:2 to 4; preferably, the activator is selected from any one or more of zinc chloride, ferrous chloride, cobalt chloride and nickel chloride.

7. The preparation method according to any one of claims 1 to 6, characterized in that In the step S1, the temperature of the calcination treatment is 600-800° C.; and / or the time of the calcination treatment is 40-80 minutes.

8. The preparation method according to any one of claims 1 to 7, characterized in that In the step S1, the impurity removal treatment includes: acid soaking, water washing and drying the product of the roasting treatment in sequence to obtain the first intermediate product; Preferably, the acid soaking reagent is selected from any one or more of hydrochloric acid solution, sulfuric acid solution, phosphoric acid solution and acetic acid solution; further preferably, the acid soaking reagent is hydrochloric acid solution, and the concentration of hydrochloric acid in the hydrochloric acid solution is 1-3 mol / L; and / or, the ratio of the mass of the calcined product to the volume of the hydrochloric acid solution is 1g:5-10gmL; and / or, the temperature of the acid soaking is 20-30°C; and / or, the time of the acid soaking is 1-2h.

9. A modified coal gangue adsorbent, characterized in that: The modified coal gangue adsorbent is prepared by the preparation method described in any one of claims 1 to 8.

10. Use of the modified coal gangue adsorbent according to claim 9 in wastewater treatment.

Citation Information

Patent Citations

  • Modified coal gangue adsorbent as well as preparation method and application thereof

    CN115646455A